Factors affecting optimal breastfeeding among health workers in the Kumasi metropolis of Ghana - Emmanuel Dubure; Reginald Adjetey Annan (Discover Public Health)
Abstract Objective To assess the prevalence and factors associated with optimal breastfeeding among health workers in the Kumasi metropolis of Ghana. Methods This was a mixed methods cross-sectional study conducted in four hospitals in Kumasi, Ghana. One hundred and eighty female health workers responded to a structured questionnaire and eight were engaged in a focus group discussion. Aspects of optimal breastfeeding assessed were early initiation of breastfeeding, exclusive breastfeeding and breastfeeding duration. Data were also collected on breastfeeding barriers and infant feeding knowledge. Descriptive statistics and odds ratios were generated for the quantitative data, and thematic analysis was conducted for the qualitative data. Results We found that most (73%) of the health workers initiated breastfeeding within one hour after delivery. However, nearly half (49%) did not practice exclusive breastfeeding for six months. Cesarean section delivery was associated with lower odds of initiating breastfeeding within one hour after birth compared to vaginal delivery (AOR = 0.10, 95% CI 0.05,0.23, p < 0.001). Early work resumption (Resuming work less than four months after delivery) reduced the odds of practicing exclusive breastfeeding for six months (AOR = 0.50, 95% CI 0.27,0.92, p = 0.026). Cesarean-section delivery, short maternity leave, family influences and work-related barriers were the themes that emerged as barriers to optimal breastfeeding. Conclusion Health workers experience work-related barriers and limited social support when breastfeeding after delivery. Therefore, policies should address these barriers to encourage optimal breastfeeding among health workers.